Social and cultural dimensions of hygiene in Cambodian health care facilities - Faurand-Tournair; Dumas Céline; Hancart-Petitet Pascale; Desclaux Alice; Vong Sirenda (BMC, 2011)
Abstract Background The frequency of bloodborne pathogen healthcare-associated infections is thought to be high in developing Southeast Asian Countries. The underlying social-cultural logics contributing to the risks of transmission are rarely studied. This report provides some insights on the social and cultural factors that shape hygiene practices in Cambodian health care settings. Methods We conducted qualitative surveys in various public and private health facilities in Phnom Penh, the capital city and in provinces. We observed and interviewed 319 participants, health care workers and patients, regarding hygiene practices and social relationships amongst the health care staff and with patients. We also examined the local perceptions of hygiene, their impact on the relationships between the health care staff and patients, and perceptions of transmission risks. Data collection stem from face to face semi-structured and open-ended interviews and focus group discussions with various health care staffs (i.e. cleaners, nurses, midwives and medical doctors) and with patients who attended the study health facilities. Results Overall responses and observations indicated that hygiene practices were burdened by the lack of adequate materials and equipements. In addition, many other factors were identified to influence and distort hygiene practices which include (1) informal and formal social rapports in hospitals, (2) major infection control roles played by the cleaners in absence of professional acknowledgment. Moreover, hygiene practices are commonly seen as an unessential matter to be devoted to low-ranking staff. Conclusion Our anthropological findings illustrate the importance of comprehensive understanding of hygiene practices; they need to be considered when designing interventions to improve infection control practices in a Cambodian medical setting.